Short-term evolution of a reflective beach sector in front of a coastal lagoon (Southwest Portuguese coast) - Gama, Cristina (2012)
Several coastal lagoon entrances are controlled by the contiguous subaerial beach that works as a detrital barrier. Hence the importance of characterizing the adjacent beach morphodynamics regarding the beachface and berm reconstruction for coastal management proposals. The studied area, a subaerial beach sector of 308 m, located in front of the Melides coastal lagoon, is placed in an embayed sandy coastline at the Portuguese Southwest Atlantic Coast. During one year (April 2010 to April 2011), 26 field surveys were conducted in order to describe the evolution of this subaerial beach sector. The periodicity of the campaigns was defined in order to characterize the effects of storms (pre and post-storm) and tides (spring and neap tides), on subaerial beach morphodynamics adjacent to the lagoon entrance. A survey grid with an alongshore length of 308m and a width defined between the lower limit of the beachface and the backshore limit (entrance of the coastal lagoon or frontal dune) was used. This grid considered 12 cross-shore profiles apart by 40 m. The alongshore profiles describes the main topographic variations (e.g. top of the beachface, berms elevation, beach cups definition). Horizontal and vertical positioning was provided by Real-Time Kinematic (RTK) GPS. The results allowed the construction of high resolution Digital Elevation Model (DEM) of the studied area. This data were used to describe in detail the beach morphologic changes using the ArcGIS software. The superficial beach sediments were also collected pointing to the predominance of coarse to very coarse sand. The nearshore wave characteristics was described by the SWAN wave model considering as boundary conditions wave data recorded at the Sines wave rider buoy. The run-up levels were calculated considering the wave parameters and the beachface slope (0.12 to 0.18, tanβ). The results obtained in field campaigns, allow the description of the morphological pattern and morphodynamic evolution of detrital barrier (conceptual model) that separates the lagoon Melides from the sea. It is clear a morphological and morphodynamic cyclic behavior of the detrital barrier, marked by an equilibrium stage characterized by a wide berm (35 m) with a berm elevation of 5m. This steady state is reached at different times; however it is characterized by the predominance of the wave overtopping process responsible by berm reconstruction. This study was funded by the Administração da Região Hidrográfica do Alentejo (ARH). Bathymetric source was provided by the General Bathymetric Chart of the Oceans (GEBCO_08 Grid,) and the wave data available from the Instituto Hidrográfico (Portugal) web site.